دور الآليات الداخلية لحوكمة الشركات في تحقيق جودة تقارير الأعمال المتكاملة: دراسة تطبيقية - أحمد، محمد مشرح علي Ahmed, Mohammed Mashrah Ali; حسن، كمال عبدالسلام علي; إسماعيل، عصام عبدالمنعم أحمد (جامعة عين شمس - كلية التجارة - قسم المحاسبة والمراجعة, 2019)
This study aimed to identify the nature and objectives of the integrated reporting and their information content, And identify the advantages and challenges of integrated reporting, And its role as a determinant to assess an entity's ability to create value over the short, medium and long term, as well as examining the impact of the internal mechanisms of corporate governance on the quality of integrated reporting. The methodology of the study is based on two axes: the first is the Deductive approach to Extract theoretical insights on how the internal mechanisms of corporate governance contribute to increasing the level of quality of integrated reporting. The second axis is the Inductive method. The researcher applied to a sample of 75 companies listed on the Johannesburg Stock Exchange Which published its integrated reporting in 2016. Six indicators were designed to measure the quality level from a perspective of (6) stakeholder groups and were based on the method of content analysis and Multiple regression models through using the statistical analysis program (SPSS V.20). The study found that there is a significant effect on the internal mechanisms of corporate governance represented by the Board of Directors, the Audit Committee and The Risk Management Committee and Internal Audit on the quality of the integrated reporting at a significant level of 5%. The study also found that the control variables represented by firm size and audit type At a significant level of 5%.
استهدفت الدراسة التعرف على طبيعة وأهداف التقارير المتكاملة ومحتواها المعلوماتي، والتعرف على المزايا والتحديات التي تواجه إعداد التقارير المتكاملة، ودورها كمحدد لتقييم قدرة المنشأة على خلق القيمة خلال المدى القصير والمتوسط والطويل، وكذلك دراسة أثر الآليات الداخلية لحوكمة الشركات على جودة التقارير المتكاملة. وتعتمد منهجية الدراسة على محورين: المحور الأول وهو المنهج الاستنباطي للخروج بتأصيل نظري حول كيفية مساهمة الآليات الداخلية لحوكمة الشركات في زيادة مستوى جودة التقارير المتكاملة، والمحور الثاني هو المنهج الاستقرائي حيث قام الباحث بالتطبيق على عينة مكونة من 75 شركة من الشركات المدرجة ببورصة جوهانسبرج بجنوب أفريقيا والمنشور تقاريرها المتكاملة عام 2016 حيث تم تصميم عدد (6) مؤشرات لقياس مستوى الجودة في التقارير المتكاملة من منظور عدد (6) مجموعات من أصحاب المصالح وتم الاعتماد على أسلوب تحليل المحتوى، ونماذج الانحدار المتعدد من خلال برنامج التحليل الإحصائي SPSS Ver.20. وتوصلت الدراسة إلى وجود تأثير معنوي للآليات الداخلية لحوكمة الشركات متمثلة في مجلس الإدارة ولجنة المراجعة ولجنة إدارة المخاطر والمراجعة الداخلية على جودة التقارير المتكاملة عند مستوى معنوية 5%. كما توصلت الدراسة إلى وجود تأثير للمتغيرات الرقابية متمثلة في حجم الشركة وحجم مكتب المراجعة على جودة التقارير المتكاملة عند مستوى معنوية 5%.
Keywords: حوكمة الشركات -- التقارير المالية -- المعلومات المحاسبية -- المراجعة الداخلية -- إدارة المخاطر